Manejo optométrico post cirugía de catarata congénita en paciente masculino de 26 años de edad. - Jara Coronel, Irene Lilibeth (2023)
In this case, the conditions of a congenital cataract and its postoperative optometric evaluation as well as its treatment are studied, and a correct follow-up for the complement of this surgery, objective tests were carried out with the help of the autorefractometer and digital keratometer where it was found as a result corneal myopia and astigmatism, in addition, through a subjective test, a loss of accommodation was found due to pseudophakia, in which it was possible to verify that due to the binocular congenital cataract various refractive errors were triggered, amblyopia developed due to poor development In the left eye, due to its delayed intervention, in terms of treatment, the use of a progressive and transition sphero-cylinder aerial lens is used, which has a progressive graduation, providing a solution in the compensation of your vision and thus being able to distinguish objects in the vicinity and far distance which, within its qualities, this ophthalmic lens allows you to do your academic work on the computer and thus perform with more ease and comfort in your day to day as well as photosensitive protection. The adaptation period of this lens was 15 days with acceptance and favorable management with efficacy on the part of the patient.